2017
DOI: 10.1186/s40694-017-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization of secondary metabolite producing Penicillium cell factories

Abstract: Background Penicillium species are important producers of bioactive secondary metabolites. However, the immense diversity of the fungal kingdom is only scarcely represented in industrial bioprocesses and the upscaling of compound production remains a costly and labor intensive challenge. In order to facilitate the development of novel secondary metabolite producing processes, two routes are typically explored: optimization of the native producer or transferring the enzymatic pathway into a heterologous host. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
(35 reference statements)
1
29
0
2
Order By: Relevance
“…By constraining the maximum specific oxygen uptake rate to 10 mmol·gDW −1 ·hr −1 and the maximum specific glucose uptake rate to 5 mmol·gDW −1 ·hr −1 ; the maximum specific growth rate was in the range 0.305–0.323 hr −1 . Similar specific growth rates have been experimentally determined measured for 10 of the 24 species where they range between 0.19 and 0.24 hr −1 in defined media with glucose as the sole carbon source (Grijseels et al, ).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…By constraining the maximum specific oxygen uptake rate to 10 mmol·gDW −1 ·hr −1 and the maximum specific glucose uptake rate to 5 mmol·gDW −1 ·hr −1 ; the maximum specific growth rate was in the range 0.305–0.323 hr −1 . Similar specific growth rates have been experimentally determined measured for 10 of the 24 species where they range between 0.19 and 0.24 hr −1 in defined media with glucose as the sole carbon source (Grijseels et al, ).…”
Section: Resultssupporting
confidence: 77%
“…They correspond to growth in a minimal media and with only a few cofactors. This minimal growth medium was designed based on experimental observations (Grijseels et al, ). For each of the 24 GEMs, a biomass function was constructed based on the biomass function of P. rubens , as described previously (Agren et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that Penicillium species have highly variable secondary metabolite production, ranging from producing 4 to 34 different identified secondary metabolites. These metabolites were often species specific, among the identified metabolites only six were shared between some of the species, none were shared between all (Grijseels et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fungal cell factories are attracting significant interest due to their biotechnological potential [ 1 , 18 , 19 , 20 ]. The strategy has been widely applied to primary metabolism towards the production of enzymes or their derived metabolites.…”
Section: Introductionmentioning
confidence: 99%